al-Akhṭā’ al-Naḥwīyah al-Shā’i‘ah fī al-Af‘āl ladá al-Mughridīn al-‘Arab fī Twitter - Nujud Ismail Alanazi; Mohd Azidan Abdul Jabar; Abdurrauf Hassan; Abdul Halim bin Mohamad (Universitas Negeri Jakarta, 2018)
Arabic is exposed to many negative linguistic manifestations, such as the phenomenon of widespread grammatical errors in social media, especially twitter. The current study aims to monitor grammatical errors in verbs twitter tweets. The study also seeks to investigate the impact of grammatical errors on the understanding of tweets and to detect the effect of grammatical errors in verbs on the Arabic level. To verify the validity of the hypotheses and to answer all the questions, the researchers will use the statistical analytical descriptive method to obtain the study data. The study will then devise a computer program designed by the researchers to correct common grammatical errors in using the verbs on twitter. The study sample will consist of only 200 informative tweets from 2016 to 2018, with many Arab political and social events occurring in this period, so twitter has become an important and influential medium in the Arab world. To come out to clear and steady numerical results for the study, and one of the most important results of the research: the prevalence of grammatical errors in the verb appeared in varying proportions, where the highest percentage of errors appeared for assertions, reaching 44%, and the lowest percentage was for payments, reaching 22%.